PROFIL KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN METAKOGNITIF SISWA BERDASARKAN JENIS KELAMIN - Rahman, Aditya (Jurnal Pendidikan Biologi, 2018)
The aim of this study was to analyze the students critical thinking competence, and metacognitive competence based on genders through the learning model of problem based learning on the concept of environmentpollution at grade X of SMA 3 Kota Serang. The poppulation of the research was all students grade X MIPA, and the sample were 40 students at X MIPA 5 SMAN 3 Kota Serang City. This research used purposive random sampling technique. The instrumen used to essay test, kuesionerand observation. Based on result of this research, there is no impact between gender difference on critical thinking competence and metacognitive competence. Critical thinking aspect of male students belongs to equals category in 64,2, critical thinking of female students belongs to equals category in 61,6.  Metacognitive competence of  male students to high category in 141, and metacognitivecompetence of female students to high category in 137. The percentage of total critical thinking competence of all students using PBL model in good and excellent category is 51%, while the percentage of students' metacognitive competence in high category is 91%.